تمثيلات الطلبة الجامعيين نحو مهنة المستقبل دراسة ميدانية في جامعة عمار ثليجي - فاطمة عطية; أشواق عطية; الأزهاري بن عيسى (My University, 2023)
The aim of the current study was to reveal the student's perceptions of his future profession. For that reason, we raised the following questions: -Has the social environment in which students live influenced the formation of their representations about the field of work? -Has university specialization influenced the formation of university student's representations towards the future profession? *Hypotheses: -The social environment is a supportive and influential factor in guiding university students' representations towards the vocational project. -The specialization is the reference for the composition of students' representations towards the profession of the future. -The social type has an impact on building students' perceptions of career. In order to achieve the study's objectives and to respond to its hypotheses, we have relied on the descriptive curriculum, observation and form tools, and to arrive at objective results. A sample of 70 students coming to graduate from Ammar Thaliji University in Agat, where we have reached the following results: The student's social mediator has made a significant impact on the formation of these representations